COVID-19 ADVERTISING LANGUAGE LOCUTIONARY, ILLOCUTIONARY AND PERLOCUTIONARY FORMS ON SOCIAL MEDIA (A SOCIOPRAGMATIC STUDY) - Abdul Rahman Rahim; Andi Syukri Syamsuri; Muhalim Muhalim; Arifuddin Arifuddin (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This study seeks to conduct an analysis of locutions, illocutions, and perlocutions within the context of the utilization of the Indonesian language in public service advertisements pertaining to the subject of Covid-19. The research conducted is classified as a qualitative descriptive study. Data for this research endeavor were collected in May 2021 through meticulous note-taking and documentation techniques. Subsequent data analysis ensued through a structured sequence of procedures, which encompassed: identification, classification, analysis, interpretation, and description, with the latter aimed at providing a comprehensive overview of the outcomes of the data analysis. The focal point of this inquiry is the realm of Public Service Advertisements that revolve around the theme of Covid-19. Our scrutiny primarily pertains to an examination of the locutionary, illocutionary, and perlocutionary dimensions of these advertisements.  Upon the thorough examination of the ten public service advertisements included in this study, spanning various mediums such as television, billboards, and social media, it was discerned that all of them shared a common objective. The locutionary aspect, serving as the foundational semantic content, predominantly conveys basic information concerning the transmission of Covid-19. In parallel, the illocutionary facet of these messages serves as a cautionary directive, imparting a sense of urgency and imparting an effect stemming from the act of speech. Furthermore, the perlocutionary dimension of these messages, specifically regarding Covid-19, invokes a call to action. This entails the necessity of disrupting the transmission chain of the Covid-19 virus while simultaneously bolstering one's immune system, rigorously implementing health protocols, and adopting measures to flatten the curve of Covid-19 transmission.